Bridging Formal Law and Customary Wisdom: A Model for Integrated Spatial Planning Control in Bali’s Tourism Sector (Lembaga Contrarius Indonesia, 2026)
The urgency of this research is to build a spatial planning control model capable of integrating spatial governance between local government, customary villages, and the private sector. This is due to the rampant violations of spatial planning in tourism investment activities, which tend to disregard local wisdom values such as Asta Kosala Kosali and Tri Hita Karana. The purpose of this research is to analyze the effectiveness of spatial planning regulations in tourism investment activities in Bali and to formulate an integrated spatial planning control system model to support local wisdom and sustainable development. The method used in this study employs a critical qualitative approach, with data collection techniques including observation, in-depth interviews with relevant agencies and stakeholders. The location was selected using purposive sampling based on tourism investment activities occurring at the research location, namely Denpasar City and Badung Regency. Data processing and analysis techniques were performed using qualitative description. The research results indicate that the integrated spatial planning control model to support sustainable tourism investment is by combining legal regulations with certainty, the existence of planning and control instruments for spatial planning that consider sustainable social and economic aspects, accompanied by coordinated governance and institutions.